Pengaruh Rasio Utang dan Budgetary Solvency Terhadap Financial Sustainability Pada Kabupaten/Kota di Provinsi Sumatera Selatan - Nadia Gracia Syakirah; Yuli Antina Aryani; Indriani Indah Astuti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the effect of laverage and budgetary solvency on financial sustainability in districts/cities in South Sumatra province. This study uses a quantitative approach with secondary data obtained from the BPK RI Audit Report (LHP) on Local Government Financial Statements (LKPD) from 2019 to 2023. The sampling technique used saturated sampling, with a total sample of 85 observations from 17 districts / cities for five years. The results showed that partially laverage has a negative effect and not significant on Financial Sustainability and budgetary solvency is found to have a significant positive effect on financial sustainability. Simultaneously, laverage and budgetary solvency have a significant effect on financial sustainability. These findings indicate that financial flexibility through laverage and budgetary solvency are key factors in the dynamics of changes in financial sustainability.